Surface and underground excavations : methods, techniques and equipment - Tatiya, Ratan (Boca Raton : CRC Press/Balkema, 2013)
'This expanded second edition is a comprehensive text on the latest technologies and developments in excavation for any type of surface or underground excavation. A great number of topics is covered, as well as excavation techniques for various operations. The book has been wholly revised, and includes the latest trends and best practices as well as questions at the end of each chapter. It is now even more appealing to students in earth sciences, geology and in civil, mining and construction engineering and those with a general or professional interest in surface and underground excavations'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Excavation; Rock excavation; Underground areas